2011
DOI: 10.1007/s00449-011-0554-7
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the production limitations of Photorhabdus temperata ssp. temperata strain K122 bioinsecticides in low-cost medium

Abstract: For low-cost production of Photorhabdus temperata ssp. temperata strain K122 bioinsecticide, a cheap complex medium was optimized. Diluted seawater was used as the source of micronutrients, especially sodium chloride, involved in the improvement of cell density, culturability and oral toxicity of the bacterium P. temperata against Ephestia kuehniella larvae. Thus, the new formulated medium was composed only of 10 g/l of soya bean meal, used as the carbon and nitrogen main source, mixed in sevenfold diluted sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…a). The enhancement of P. temperata toxin synthesis through NaCl addition was demonstrated by Jallouli et al (2011). Indeed, an improvement of 81.4 and 42.22 % of P. temperata oral toxicity in CM and OM, respectively was obtained when NaCl was added beyond 2 g/l.…”
Section: Response Surface Methodology: Box-behnken Designmentioning
confidence: 92%
See 3 more Smart Citations
“…a). The enhancement of P. temperata toxin synthesis through NaCl addition was demonstrated by Jallouli et al (2011). Indeed, an improvement of 81.4 and 42.22 % of P. temperata oral toxicity in CM and OM, respectively was obtained when NaCl was added beyond 2 g/l.…”
Section: Response Surface Methodology: Box-behnken Designmentioning
confidence: 92%
“…Similarly, previous studies reported that addition of sodium chloride at 5 g/l to OM and CM doubles biomass production of the strain K122 of P. temperata. NaCl was demonstrated to be a stimulator of growth of the strain K122 by increasing nutrients assimilation (Jallouli et al 2011). In addition, Jallouli et al (2012) demonstrated that biomass production increased with the increase in inoculum size.…”
Section: Response Surface Methodology: Box-behnken Designmentioning
confidence: 94%
See 2 more Smart Citations
“…Indeed, oral toxicity, assessed as the growth inhibition of E. kuehniella larvae fed with P. temperata K122 at 4 Â 10 8 cells/ml, was 27%, when cultured in the optimized medium (OM) (Jallouli et al, 2008). Several studies have been already carried out to improve toxicity of P. temperata K122 by avoiding Vsm polymorphism (Jallouli et al, 2008) and addition of sodium chloride at 5 g/l (Jallouli et al, 2011). Improvement could be achieved also by control of the dissolved oxygen concentration during the fermentation process using the OM or the complex medium.…”
Section: Introductionmentioning
confidence: 99%